Description of a new species of Bibrax Fletcher from Colombia with an updated diagnosis and key to species (Coleoptera, Staphylinidae, Pselaphinae) - Asenjo, Angélico; Lozada, Clara Milena Concha; Ropero, Maria Cristina Gallego; Gouvea, Bruno (Zootaxa, 2024)
Bibrax popeye Asenjo, Concha-Lozada, Gallego-Ropero & Gouvea, sp. nov., of the Neotropical Pselaphinae of the tribe Metopiasini, is described from the department of Cauca in southeastern Colombia. Diagnosis is provided for the genus and new species; with illustrations of the major diagnosis features, a key to the known species, and a distribution map.